Amyotrophic lateral sclerosis diagnostic index: Toward a personalized diagnosis of ALS. (5th February 2019) - Geevasinga, Nimeshan; Howells, James; Menon, Parvathi; van den Bos, Mehdi; Shibuya, Kazumoto; Matamala, José Manuel; Park, Susanna B.; Byth, Karen; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objective: The aim of the study was to assess the utility of a novel amyotrophic lateral sclerosis (ALS) diagnostic index (ALSDI). Methods: A prospective multicenter study was undertaken on patients presenting with suspected ALS. The reference standard (Awaji criteria) was applied to all patients at recruitment. Patients were randomly assigned to a training (75%) and a test (25%) cohort. The ALSDI was developed in the training cohort and its diagnostic utility was subsequently assessed in the test cohort. Results: A total of 407 patients were recruited, with 305 patients subsequently diagnosed with ALS and 102 with a non-ALS mimicking disorder. The ALSDI reliably differentiated ALS from neuromuscular disorders in the training cohort (area under the curve 0.92, 95% confidence interval 0.89–0.95), with ALSDI ≥4 exhibiting 81.6% sensitivity, 89.6% specificity, and 83.5% diagnostic accuracy. The ALSDI diagnostic utility was confirmed in the test cohort (area under the curve 0.90, 95% confidence interval 0.84–0.97), with ALSDI ≥4 exhibiting 83.3% sensitivity, 84% specificity, and 83.5% diagnostic accuracy. In addition, the diagnostic utility of the ALSDI was confirmed in patients who were Awaji negative at recruitment and in those exhibiting a predominantly lower motor neuron phenotype. Conclusion: The ALSDI reliably differentiates ALS from mimicking disorders at an early stage in the disease process. Classification of evidence: This study provides Class I evidence that for patients with suspected ALS, the ALSDI distinguished ALS from neuromuscular mimicking disorders.